Effect of compliance to continuous positive airway pressure on exacerbations, lung function and symptoms in patients with chronic obstructive pulmonary disease and obstructive sleep apnea (overlap syndrome). (12th January 2023) - Voulgaris, Athanasios; Archontogeorgis, Kostas; Anevlavis, Stavros; Fanaridis, Michail; Froudarakis, Marios E.; Schiza, Sofia; Steiropoulos, Paschalis
Abstract: Introduction: Patients with overlap syndrome (OS), that is obstructive sleep apnea (OSA) and chronic obstructive pulmonary disease (COPD), are at increased risk of acute exacerbations related to COPD (AECOPD). We assessed the effect of CPAP compliance on AECOPD, symptoms and pulmonary function in OS patients. Methods: Consecutive OS patients underwent assessment at baseline and at 12 months under treatment with CPAP of: AECOPD and hospitalizations, COPD Assessment Test (CAT) and modified British Medical Research Council (mMRC) questionnaires, pulmonary function testing and 6‐min walking test (6MWT). Results: In total, 59 patients (54 males) with OS were followed for 12 months and divided post hoc according to CPAP compliance into: group A with good (≥4 h CPAP use/night, n = 29) and group B with poor (<4 h CPAP use/night, n = 30) CPAP compliance. At 12 months, group A showed improvements in FEV1 ( p = 0.024), total lung capacity ( p = 0.024), RV/TLC ( p = 0.003), 6MWT ( p < 0.001) and CAT ( p < 0.001). COPD exacerbations decreased in patients with good CPAP compliance from baseline to 12 months (17 before vs. 5 after, p = 0.001), but not in those with poor compliance (15 before vs. 15 after, p = 1). At multivariate regression analysis, COPD exacerbations were associated with poor CPAP compliance (β = 0.362, 95% CI: 0.075–0.649, p = 0.015). Conclusions: When compared to poorly compliant patients, OS patients with good CPAP compliance had a lower number of AECOPD and showed improved lung function and COPD related symptoms. Abstract : This study assessed the effects of continuous positive airway pressure (CPAP) compliance on acute exacerbations of COPD, symptoms and pulmonary function in patients with overlap syndrome (OS). In total, 59 patients (54 males) with OS were followed for 12 months and divided post hoc according to CPAP compliance into those with good (≥4 h CPAP use/night, n = 29) and those with poor (<4 h CPAP use/night, n = 30) CPAP compliance. COPD exacerbations decreased in patients with good CPAP compliance from baseline to 12 months (17 before vs. 5 after, p = 0.001), but not in those with poor compliance (15 before vs. 15 after, p = 1).